Sistem Informasi E-Commerce Rumah Batik Desa Lambur 1 Tanjung Jabung Timur - Susanto, Susanto; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2022)
Rumah Batik is a sales shop that is engaged in making batik such as various types of batik typical of Tanjung Jabung Timur, batik basic fabrics and community handicrafts, at Rumah Batik has obstacles in marketing their wares, because currently Rumah Batik customers only come directly to visit. stores to purchase products, as well as product promotions only by word of mouth and brochures, at a distance from the house far from the store location. So an E-commerce information system was designed at the Batik House of Lambur 1 Tanjung Jabung Timur Village with the aim of making it easier to order products, increase sales, and reduce promotional costs. In this study using prototyping modeling, it is hoped that the results of this study make it easier for customers to make purchases, order and confirm payments. Make it easy for administrators to manage goods data, order data and product purchases. For the future, the analysis and design of the designed E-commerce system can be used at the Batik House of Lambur 1 Tanjung Jabung Timur Village.